ANALISIS PENGARUH GENDER TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV PADA MATA PELAJARAN IPS - Hamidah, Fitria; Sarifah, Iva; Banindra Yudha, Chrisnaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to examine the effect of gender on critical thinking skills in social studies subjects at SDN Kebon Jeruk 08 West Jakarta. The sample in this study was 32 class IV students consisting of 15 male students and 17 female students. The instruments used to measure students' critical thinking abilities are in the form of questionnaires and multiple-choice questions. Based on the research results, it can be concluded that there is an influence between gender on critical thinking skills. The influence of gender on students' critical thinking skills in social studies subjects is quite high. Female students have better critical thinking skills than male students. Keywords: critical thinking skills, gender, social sciences